The effect of biodegradation on surface and bulk property changes of polypropylene, recycled polypropylene and polylactide biocomposites - Strömberg, Emma; Karlsson, Sigbritt (International biodeterioration & biodegradation, 2009)
Biocomposites were subject to exposure to a mixture of fungi and algae in a microenvironment chamber. Surface and bulk property changes of polypropylene/wood flour, recycled polypropylene/cellulose and polylactide/wood flour were monitored by tensile testing, Differential Scanning Calorimetry (DSC), Thermal Gravimetric Analysis (TGA) and Field Emission Scanning Electron Microscope (FE-SEM). All the biocomposites showed a substantial decrease in toughness after 28 and 56 days of hydrolysis. The ductility increased after 28 and 56 days, but deteriorated after 84 days of hydrolysis. Biofilm formation occurred on all biocomposites even if the polymer itself was inert to biodegradation. The microbial colonization affected mainly the surface properties of polypropylene biocomposites while changes were monitored also in the bulk properties of polylactide biocomposites. The cellulose fibres in the composites gave a more easily colonized surface mainly attributed to water uptake. In the short term perspective, the water uptake offered better conditions for biofilm adhesion, and in the longer perspective the exposure to microorganisms also resulted in mechanical degradation, followed by biodegradation of cellulose. With time this will leave a porous matrix of polypropylene, while biodegradable polymers such as polylactide will degrade in parallel with the fibre part.